MUTASI EGFR PADA PEMERIKSAAN SITOLOGI ADENOKARSINOMA PARU - Ika Kustiyah Oktaviyanti (Fakultas Kedokteran Universitas Lambung Mangkurat, 2015)
The case of lung cancer increased lately. World Health Organization (WHO) include lung cancer as one of the major problems facing the world in this decade, as more than 1.1 million people died from the disease. In histopathology, lung cancer is divided into several types, one of which is Adenocarcinoma. Various therapies developed to improve survival in patients with lung cancer, and recently also developed a therapeutic gene targets, one of which is the anti-EGFR. However, this therapy needs to be examination of the EGFR gene mutation, because the anti-EGFR therapy would respond in patients with EGFR gene mutation. This study aims to see how the pattern of EGFR mutations, and their relation to age, sex, and smoking habits. Research samples taken from pleural fluid cytology or biopsy of the tumor with fine needle aspiration, then examined whether there is an EGFR mutation. In this study, obtained 38 samples of patients with Adenocarcinoma of the lung, where 34% of patients had mutations in the gene EGFR, which consisted of 7 patients had mutations deletion in exon 19, 1 patients with mutations in exon 21L86IQ, 4 patients experienced EGFR mutations in exons 21L858R, and contained 1 those patients who had mutations in two places, namely in exon 19 and exon 21L861Q. EGFR mutations are many in the age range 40-49 years, but there is no relationship between the age of the patient with the presence and absence of mutations in the EGFR gene. In this study there was no difference between men and women who have EGFR mutations, but women with lung adenocarcinoma more mutated in EGFR. On this study, patients who did not smoke more EGFR mutations (51%) compared to the active smoking (10%). Keywords: lung adenocarcinoma, EGFR mutations